Simulating plant invasion dynamics in mountain ecosystems under global change scenarios. (21st September 2017) - Carboni, Marta; Guéguen, Maya; Barros, Ceres; Georges, Damien; Boulangeat, Isabelle; Douzet, Rolland; Dullinger, Stefan; Klonner, Guenther; van Kleunen, Mark; Essl, Franz; Bossdorf, Oliver; Haeuser, Emily; et al.
Abstract: Across the globe, invasive alien species cause severe environmental changes, altering species composition and ecosystem functions. So far, mountain areas have mostly been spared from large‐scale invasions. However, climate change, land‐use abandonment, the development of tourism and the increasing ornamental trade will weaken the barriers to invasions in these systems. Understanding how alien species will react and how native communities will influence their success is thus of prime importance in a management perspective. Here, we used a spatially and temporally explicit simulation model to forecast invasion risks in a protected mountain area in the French Alps under future conditions. We combined scenarios of climate change, land‐use abandonment and tourism‐linked increases in propagule pressure to test if the spread of alien species in the region will increase in the future. We modelled already naturalized alien species and new ornamental plants, accounting for interactions among global change components, and also competition with the native vegetation. Our results show that propagule pressure and climate change will interact to increase overall species richness of both naturalized aliens and new ornamentals, as well as their upper elevational limits and regional range‐sizes. Under climate change, woody aliens are predicted to more than double in range‐size and herbaceous species to occupy up to 20% of the park area. In contrast, land‐use abandonment will open new invasion opportunities for woody aliens, but decrease invasion probability for naturalized and ornamental alien herbs as a consequence of colonization by native trees. This emphasizes the importance of interactions with the native vegetation either for facilitating or potentially for curbing invasions. Overall, our work highlights an additional and previously underestimated threat for the fragile mountain flora of the Alps already facing climate changes, land‐use transformations and overexploitation by tourism. Abstract : Climate change, land‐use abandonment, tourism and increasing ornamental trade are currently weakening barriers to alien plant invasions in mountain areas. We used a dynamic simulation model to forecast future invasion risks in a protected area in the French Alps, showing that propagule pressure and climate change will increase species richness, maximum elevation and regional range‐sizes of established aliens and newly introduced ornamental plants. Abandonment will open opportunities for woody aliens, but decrease invasion probability for herbs as a consequence of colonization by native trees. Our work anticipates a previously underestimated threat for the fragile mountain flora of the Alps.